Determination of Biological Treatability Processes of Textile Wastewater and Implementation of a Fuzzy Logic Model - Harun Akif Kabuk; Yasar Avsar; S. Levent Kuzu; Fatih Ilhan; Kubra Ulucan (International Journal of Photoenergy)
This study investigated the biological treatability of textile wastewater. For this purpose, a membrane bioreactor (MBR) was utilized for biological treatment after the ozonation process. Due to the refractory organic contents of textile wastewater that has a low biodegradability capacity, ozonation was implemented as an advanced oxidation process prior to the MBR system to increase the biodegradability of the wastewater. Textile wastewater, oxidized by ozonation, was fed to the MBR at different hydraulic retention times (HRT). During the process, color, chemical oxygen demand (COD), and biochemical oxygen demand (BOD) removal efficiencies were monitored for 24-hour, 12-hour, 6-hour, and 3-hour retention times. Under these conditions, 94% color, 65% COD, and 55% BOD removal efficiencies were obtained in the MBR system. The experimental outputs were modeled with multiple linear regressions (MLR) and fuzzy logic. MLR results suggested that color removal is more related to COD removal relative to BOD removal. A surface map of this issue was prepared with a fuzzy logic model. Furthermore, fuzzy logic was employed to the whole modeling of the biological system treatment. Determination coefficients for COD, BOD, and color removal efficiencies were 0.96, 0.97, and 0.92, respectively.